Targeted Antimicrobial Photochemotherapy - Soukos, Nikolaos S. (American Society for Microbiology, 1998)
This study explores a new approach for antimicrobial therapy with light activation of targeted poly-l-lysine (pL)–chlorin e6 (c(e6)) conjugates. The goal was to test the hypothesis that these conjugates between pL and c(e6) would efficiently target photodestruction towards gram-positive (Actinomyces viscosus) and gram-negative (Porphyromonas gingivalis) oral species while sparing an oral epithelial cell line (HCPC-1). Conjugates of c(e6) with pL (average molecular weight, 2,000) having a positive, neutral, or negative charge were prepared. Illumination with red light (λ(max) = 671 nm) from a diode array produced a dose-dependent loss of CFU from the bacteria, under conditions that did not affect the viability of the epithelial cells. For P. gingivalis, the cationic conjugate produced 99% killing, while the neutral conjugate killed 91% and the anionic conjugate killed 76% after 1 min of incubation and exposure to red light for 10 min. For A. viscosus, the cationic conjugate produced >99.99% killing while HCPC-1 cells remained intact. The importance of the positive charge was shown by the effectiveness of c(e6)-monoethylenediamine monoamide (a monocationic derivative of c(e6)) in killing both bacteria. The clinically employed benzoporphyrin derivative under the same conditions killed epithelial cells while leaving P. gingivalis relatively unharmed. A mixture of c(e6) with pL did not show phototoxicity comparable with that of the cationic conjugate. These results were explained by the selective uptake of the conjugates by bacteria (20- to 100-fold) compared to that by mammalian cells, while free c(e6) showed much less selectivity for bacteria (5- to 20-fold). The data suggest that the cationic pL-c(e6) conjugate may have an application for the photodynamic therapy of periodontal disease.